Sterile insect technique for key agricultural pests in Africa: successes, challenges, and future opportunities - Michael M. Githae; Reyard Mutamiswa; Pascal O. Aigbedion-Atalor; Megan Mulcahy; Candice A. Coombes; Sean D. Moore; Martin P. Hill (Crop Protection, 2026)

RPGRorf15 nanopore long-read sequencing improves retinitis pigmentosa molecular diagnosis for men and women - Manon Fabard; Aurore Devos; Anaïs F. Poncet; Jean-Pascal Meneboo; Martin Figeac; Céline Villenet; Isabelle Drumare; Sabine Defoort-Dhellemmes; Isabelle Meunier; Xavier Zanlonghi; Olivier Grunewald; Vincent Huin; et al. (Human Genetics, 2026)
RPGR (Retinitis Pigmentosa GTPase Regulator ) is the main gene involved in X-linked retinitis pigmentosa (RP) and up to 28% of sporadic RP. Pathogenic variants are mostly located in its retina-specific transcript, RPGRorf15 , especially in the terminal exon named open reading frame 15 (ORF15) , which is a highly repeated region. Because of this complex sequence, first- and second-generation short-read sequencing are difficult, both for male patients and for affected and relative females, resulting in numerous unresolved cases. Long-read sequencing appears to be the most appropriate to counter this problem. Using Oxford Nanopore Technology sequencing, we analysed 194 patients with retinal dystrophy (RD) (142 men and 52 women) suspected to be either X-linked ( n = 42) or autosomal ( n = 152), and for whom first-line sequencing of 230 retinal dystrophy genes, including RP2 and RPGRex1-19 , was negative. Pathogenic ORF15 variants were found in 27 patients (13.9%), 21 men and 6 women. Of the 42 XLRD patients, 15 were carriers (35.7%), nine men and six women, most of them had rod-cone dystrophy. Of the 152 patients with isolated RD, only 12 carried ORF15 variants (7.9%),all male patients, most of them had cone-rod dystrophy (41.7%). We demonstrate the efficacy of this technology to diagnose male cases with a family history of X-linked RD, as well as sporadic cases clinically not suggestive of ORF15 . We also show how easy it is to analyse female carriers or affected women. We expect that more heterozygous women with severe disease and no family history will be identified by this technique in the future.

Clinical-pharmacological medication reviews for insurants of a German statutory health insurance fund (Kaufmännische Krankenkasse (KKH)): a 5-year retrospective analysis (2019–2023) - Johannes Heck; Dirk O. Stichtenoth; Lutz Herbarth; Christoph Schröder; Ruxandra Sabau; Thorben Pape; Sebastian Schröder; Benjamin Krichevsky; Martin Schulze Westhoff; Martin Klietz; Stephan Greten; Patrick-Pascal Strunz; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
This study sought to evaluate the characteristics of clinical-pharmacological (CP) medication reviews conducted by the Institute for Clinical Pharmacology of Hannover Medical School for older, multimorbid, polymedicated insurants of the German statutory health insurance fund Kaufmännische Krankenkasse (KKH). Special emphasis was put on potential sex-specific differences between female and male insurants, prescriptions of potentially inappropriate medications for older individuals (PIMs), and potentially inappropriate duplicate prescriptions (PIDPs). Medication reviews conducted for KKH insurants between 2019 and 2023 ( n = 334) were analyzed retrospectively. Clinical trial number is not applicable. The median age of KKH insurants (58.1% female) was 74 years (first quartile (Q1): 68; third quartile (Q3): 80). Insurants displayed a median of 7 diseases (Q1: 5; Q3: 9) and took a median of 13 drugs (Q1: 11; Q3: 16). A median of 4 CP recommendations was issued per medication review (Q1: 3; Q3: 5). The number of CP recommendations was significantly higher for female compared to male insurants (median of 4 (Q1: 3; Q3: 6) vs. median of 3 recommendations (Q1: 2; Q3: 4); p < 0.001), while the number of drugs was identical and the number of diagnoses was higher for female insurants. The most frequently prescribed PIMs were tricyclic antidepressants, benzodiazepines, and Z-drugs. At least one PIDP was detected in 16.5% of medication reviews. The sex-specific difference in the number of CP recommendations between female and male insurants may point to an unmet pharmacotherapeutic need in older women. PIM prescriptions and PIDPs were relevant topics of CP recommendations, suggesting possibilities for pharmacotherapeutic optimization in older, multimorbid, polymedicated patients.

Heterospecific social behavior in primates: insights into the evolutionary roots of pet-keeping - Cyril C. Grueter; Fany Roncin; K. Anne-Isola Nekaris; Jill Pruetz; Richard McFarland; Sabit Hasan; Malgorzata Arlet; Timothy M. Eppley; Susan M. Cheyne; Vincent Nijman; Eckhard W. Heymann; Pascal R. Marty; et al. (Primates, 2026)
Primate interspecific interactions with both other primates and non-primate species range from predator–prey dynamics to affiliative behaviors such as grooming, play, and carrying. While many primates participate in interspecific associations or commensal relationships, to our knowledge interspecific social interactions have never been systematically synthesized. Here, we present the first comprehensive review of such interactions, compiling 427 cases from the literature, media sources, and a global survey of primatologists. These involved 88 primate species and 127 non-primate species (including mammals, birds, reptiles, amphibians, malacostracans, and insects) across wild (n = 311) and captive (n = 111) contexts. The most frequent interactions occurred within or between primate families (e.g., Cercopithecidae–Cercopithecidae, Cebidae–Atelidae), though affiliative behaviors were also directed toward distantly related taxa such as dogs and birds. Play (n = 139) and grooming (n = 136) were most common. Juveniles and infants predominantly engaged in play, while adult females were more likely to groom. Adult males were less affiliative overall. Contrary to expectations, affiliative behaviors were not more often directed toward immature than adult heterospecifics. Primates were the initiators in most interactions. These findings offer new insights into the diversity and contexts of heterospecific sociality in primates and suggest that some behavioral tendencies relevant to later forms of human–animal companionship – such as caregiving, tolerance, and exploratory play – may be more widespread among primates than previously recognized.

Fate of persistent and mobile substances in drinking water treatment: A systematic comparison of treatment options - Pia Schumann; Luisa Rabe; Malte Zamzow; Isabelle Neuwald; Thomas P. Knepper; Matthias Muschket; Daniel Zahn; Pascal Hasselder; Thorsten Reemtsma; Martin Jekel; Aki Sebastian Ruhl (Journal of Hazardous Materials, 2026)

When South Meets North: A Joint Contact Zone Coinciding With Environmental Gradients in Three Boreal Tree Species - Pilar Herrera‐Egoavil; J. Luis Leal; Qiujie Zhou; Pascal Milesi; Martin Lascoux; Burçin Yıldırım (Molecular Ecology, 2026)
Post‐glacial recolonisation of Fennoscandia created secondary contact zones in many species, offering opportunities to study how gene flow and selection contribute to their establishment and maintenance. Here, we analyse genomic data from three boreal tree species— Picea abies , Betula pendula and Pinus sylvestris —sampled along a latitudinal gradient in Sweden. Despite differences in colonisation timing and dispersal ecology, all three species exhibit north–south genetic structuring aligned with environmental gradients. Most notably, the two main genetic clusters within each species overlap in a shared contact zone, corresponding to the climatic transition between Sweden's two major environmental zones. The extent and structure of the contact zone differ among species: P. abies shows stronger genetic structure and moderate gene flow, B. pendula exhibits intermediate differentiation and gene flow, and P. sylvestris displays the weakest structure with stronger gene flow. All three species also show genomic signatures of local adaptation, with distinct underlying architectures. In P. abies , adaptive loci are broadly distributed across the genome, while, strikingly, they are mostly found within an inversion on chromosome 1 in B. pendula . In P. sylvestris , local adaptation likely relies on subtle allele frequency shifts across many loci with weak signals. These patterns align with theoretical expectations for polygenic local adaptation under varying migration regimes. Our comparative approach demonstrates how gene flow and selection jointly shape genomic landscapes in shared environments and contribute to understanding local adaptation in forest trees, with implications for predicting species' responses to climate change.

Patient-derived complex organoids are a critical tool to understand and explore pediatric malignant brain tumors - Marlène Deschuyter; Sophie Martin; Chinar Salmanli; Clémence Hubsch; Audrey Vincent; Samuel Meignan; Alessandro Furlan; Erika Cosset; Hélène Burckel; Georges Noel; Michel Salzet; Marie Duhamel; et al. (Cancer and Metastasis Reviews, 2026)

The responsibility of Western European coastal states for the conservation of two emblematic migratory seabirds in the context of offshore wind farms - Alice Bernard; Nicolas Courbin; Jérémy Tornos; Tristan J.B. Martin; Mathilde Lejeune; Aurélien Prudor; Pascal Provost; Adrien Lambrechts; Chris P. Gaskin; Jérôme Cabelguen; Matthieu Bécot; Frédéric Jiguet; et al. (Biological Conservation, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Spatial and Temporal Variation in Wave Overtopping Across a Coastal Structure Based on One Year of Field Observations - Jennifer Brown; Gerd Masselink; Margaret Yelland; Christopher Stokes; Timothy Poate; Robin Pascal; David Jones; John Walk; Christopher Cardwell; Barry Martin; Peter Ganderton; Julie Gregory; et al. (Journal of Marine Science and Engineering, 2025)
Coastal managers worldwide must prepare for changes in annual wave overtopping events due to climate change and sea-level rise. Research often assesses overtopping discharges by extreme events at a sea wall crest, typically using data from physical models or empirical rules based on scaled experiments. Here, we analyse a unique 1-year field dataset of coastal wave overtopping, from SW England, to determine the number of individual waves, regardless of their size, overtopping two locations across a coastal structure. The coastal conditions causing the most frequent overtopping differ from those driving it landward, complicating hazard communications for multiuse infrastructure. These data are the first field observations covering a year of tide, wave and wind conditions that cause overtopping of a vertical sea wall. Storms have a minimal (

Healthy soils as a booster to EU competitiveness - Panos Panagos; Alberto Orgiazzi; Emanuele Lugato; Guillaume Vandenesch; Laurent Thannberger; Jason C. Neff; Arjan Reijneveld; Erik Mathijs; Pascal Chapot; Sara Guerrini; Darina Štyriaková; Julian Kremers; et al. (Land Use Policy, 2025)

The role of barrier reef protection to storm surge during tropical cyclones in a narrow lagoon, New Caledonia, south west Pacific - Maxime Duphil; Jérôme Lefèvre; Swen Jullien; Jean Roger; Pascal Dumas; Romain Le Gendre; Jérôme Aucan; Myriam Vendé-Leclerc; Martin Bénébig; Christophe Menkes (Continental Shelf Research, 2025)

How Vulnerable Are Plants to Land‐Use and Climate Changes? Comparing Current and Future Distributions at the Regional Scale According to Native and Red List Statuses - Arthur Sanguet; Nicolas Wyler; Blaise Petitpierre; Pascal Martin; Michelle Price; Antoine Adde; Anthony Lehmann (Journal of Biogeography, 2025)
Aim Future species distributions were modelled to assess the distributional changes of 1692 plant species according to several scenarios. Species vulnerability was calculated according to their red list and native statuses using a new index to better understand the most vulnerable groups of species to future conditions and improve conservation actions. Location Greater Geneva region between France and Switzerland. Time Period From present to 2050. Major Taxa Studied A total of 1692 species of plants from all major groups. Methods Two different species distribution models were created to combine the effect of climate change at the continental scale and land‐use changes at the regional scale in 2050. Two scenarios of climate change were used (optimistic and pessimistic) and one business‐as‐usual land‐use–land‐cover scenario. Current and future distributions were compared using six spatial indicators combined to create a new vulnerability index to global changes. Results More than one‐third of all species assessed showed at least a moderate vulnerability, and more than 10% showed a high vulnerability to global changes, mostly composed of native species. Most exotic species showed moderate benefits to global changes, and one‐third were associated with high benefits. Pessimistic scenarios of climate change exacerbated the trends identified under optimistic scenarios and were associated with higher vulnerability for native species and higher benefits for exotic ones. No clear pattern was found when comparing species vulnerability according to their red list status, questioning its ability to preserve species in the long term. Main Conclusions Native species are more vulnerable to global changes, while exotic species benefit from them. Climate is the main driver of future distributional changes in the study area. Current levels of threat fail to inform us of species vulnerability to future conditions, questioning their relevance and supporting the assessments of similar studies to identify the most vulnerable species.

Examining the key roles of reforestation and termite mounds on soil properties and biodiversity in an agroforestry system in Cambodia - Arun Martin; Ratha Muon; Nachy Ly; Pascal Jouquet (Agroforestry Systems, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Bonobo (Pan paniscus) Density and Distribution in Central Africa's Largest Rainforest Reserve: Long-term Survey Data Show Pitfalls in Methodological Approaches and Call for Vigilance - Mattia Bessone; Hjalmar S. Kühl; Ilka Herbinger; Gottfried Hohmann; Kouamé Paul N’Goran; Papy Asanzi; Stephen Blake; Michel Basele; Martin Bofeko; Nono Bondjengo; Pitshou Wangongo Bondo; Rigobert Booto; et al. (International Journal of Primatology, 2025)
Conservation measures require accurate estimates of density and abundance and population trend assessments. The bonobo ( Pan paniscus ) is considered Endangered in the IUCN Red List. This classification assumes that available population data are representative. However, with only 30% of the bonobo’s historic geographical range surveyed, reliable information is needed to assess the species' population status. Here, we use information from 13 surveys conducted between 2002 and 2018 in an area of 42,000 km 2 , representing ~27% of bonobo-suitable habitat: Salonga National Park and its corridor, Democratic Republic of the Congo (DRC). Using 8310 km of reconnaissance and transect walks and 27,045 days of camera trapping, we: (1) provide updated estimates of bonobo population density and distribution (42,000 km 2 ; ~5,000 km 2 of which, to the best of our knowledge, have not been surveyed before by scientists), (2) assess population trends (15,758 km 2 ; 2002–2008 vs 2012–2018), (3) compare estimates obtained with different methods, and (4) assess the factors driving bonobo density and distribution. Although we detected a non-significant population decline, our study suggests that Salonga is a bonobo stronghold, with a population ranging between 8244 and 18,308 mature individuals (density: 0.31 individuals/km 2 ). Standing crop nest counts returned non-significantly lower density estimates than camera trap distance sampling. Nest count-estimates were higher in areas with Marantaceae understorey and those farther away from rivers, while camera trap-estimates were higher in areas with lower human presence. Regardless of the method, bonobos were rarer in proximity to villages. They occurred more often in areas of dense forest cover and in proximity to ranger posts. Our results point towards a declining bonobo population in Salonga, but do not provide sufficient evidence to confirm this statistically. Consequently, the continued monitoring of the bonobo population and preservation of the integrity of Salonga, considering its biological and cultural heritage, will be crucial in the preservation of this stronghold of wild bonobos.

An approach to Molten Salt Reactor operation and control and its application to the ARAMIS actinide burner - Martin Mascaron; Johann Martinet; Vincent Pascal; Elsa Merle; Frédéric Bertrand (Annals of Nuclear Energy, 2025)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Draw me an oxidoreductase reacting with quinones - Marianne Broc; Michael V. Cherrier; Alexandre Uzel; Rodrigo Arias-Cartin; Pascal Arnoux; Gaël Brasseur; Farida Seduk; Bruno Guigliarelli; Stéphane Grimaldi; Pierre Legrand; Fabien Pierrel; Guy Schoen; et al. (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Recurrent hybridization and gene flow shaped Norway and Siberian spruce evolutionary history over multiple glacial cycles - Qiujie Zhou; Piyal Karunarathne; Lili Andersson‐Li; Chen Chen; Lars Opgenoorth; Katrin Heer; Andrea Piotti; Giovanni Giuseppe Vendramin; Elena Nakvasina; Martin Lascoux; Pascal Milesi (Molecular Ecology, 2024)
Most tree species underwent cycles of contraction and expansion during the Quaternary. These cycles led to an ancient and complex genetic structure that has since been affected by extensive gene flow and by strong local adaptation. The extent to which hybridization played a role in this multi‐layered genetic structure is important to be investigated. To study the effect of hybridization on the joint population genetic structure of two dominant species of the Eurasian boreal forest, Picea abies and P. obovata , we used targeted resequencing and obtained around 480 K nuclear SNPs and 87 chloroplast SNPs in 542 individuals sampled across most of their distribution ranges. Despite extensive gene flow and a clear pattern of Isolation‐by‐Distance, distinct genetic clusters emerged, indicating the presence of barriers and corridors to migration. Two cryptic refugia located in the large hybrid zone between the two species played a critical role in shaping their current distributions. The two species repeatedly hybridized during the Pleistocene and the direction of introgression depended on latitude. Our study suggests that hybridization helped both species to overcome main shifts in their distribution ranges during glacial cycles and highlights the importance of considering whole species complex instead of separate entities to retrieve complex demographic histories.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Combining X-ray micro-CT and microscopy-based images of two lianas species to derive structural, mechanical and functional relationships - Claudine Karlen; Pascal Turberg; Alexandre Buttler; Océane Martin; Fritz Schweingruber; Anastasios P. Vassilopoulos (Plant Systematics and Evolution, 2024)
This paper presents a biomechanical study of stems of two liana species, Clematis vitalba and Vitis vinifera , investigates the mechanical performance of these two liana species and attempts to enhance the understanding of structure–function relationships. The investigation involved mechanical testing of whole plant stems, supplemented by X-ray micro-CT (X-ray computed tomography at micron voxel size) imaging and 2D microscopic images of stained cross sections of the plant stems, to derive structure–function relationships with potential for application in bioinspired composite materials. The micro-CT images were compared to the microscopic images of stained cross sections, in order to show benefits and potential drawbacks of the X-ray micro-CT method with respect to traditional methods. The high-resolution 3D imaging capacity of micro-CT is exploited to explain the structural functionality derived from the mechanical testing. A simple finite element model is developed based on the plant topology derived by the micro-CT images and proved accurate enough to model the plant’s mechanical behaviour and assess the influence of their structural differences. The two plants exhibit different to each other physical and mechanical properties (density, strength and stiffness) due to their common growth form. Anatomical cross-sectional observation and X-ray micro-CT provide complementary information. The first method allows the identification of the lignified parts, supposedly more resistant mechanically, of these structures, while the second one provides a full 3D model of the structure, admittedly less detailed but providing the spatial distribution of density contrasts supposed to be important in the mechanical properties of the plant. The proposed methodological approach opens new perspectives to better understand the mechanical behaviour of the complex structure of plants and to draw inspiration from it in structural engineering.

Hybridization mediated range expansion and climate change resilience in two keystone tree species of boreal forests - Piyal Karunarathne; Qiujie Zhou; Martin Lascoux; Pascal Milesi (Global Change Biology, 2024)
Current global climate change is expected to affect biodiversity negatively at all scales leading to mass biodiversity loss. Many studies have shown that the distribution of allele frequencies across a species' range is often influenced by specific genetic loci associated with local environmental variables. This association reflects local adaptation and allele changes at those loci could thereby contribute to the evolutionary response to climate change. However, predicting how species will adapt to climate change from this type of data alone remains challenging. In the present study, we combined exome capture sequences and environmental niche reconstruction, to test multiple methods for assessing local adaptation and climate resilience in two widely distributed conifers, Norway spruce and Siberian spruce. Both species are keystone species of the boreal forest and share a vast hybrid zone. We show that local adaptation in conifers can be detected through allele frequency variation, population‐level ecological preferences, and historical niche movement. Moreover, we integrated genetic and ecological information into genetic offset predictive models to show that hybridization plays a central role in expanding the niche breadth of the two conifer species and may help both species to cope better with future changing climates. This joint genetic and ecological analysis also identified spruce populations that are at risk under current climate change.

Demography of endangered juvenile green turtles in face of environmental changes: 10 years of capture-mark-recapture efforts in Martinique - Pierre Lelong; Aurélien Besnard; Marc Girondot; Caroline Habold; Fabienne Priam; Mathieu Giraudeau; Guillaume Le Loc'h; Aurélie Le Loc'h; Pascal Fournier; Christine Fournier-Chambrillon; Paco Bustamante; Sophie M. Dupont; et al. (Biological Conservation, 2024)

Sperm-borne tsRNAs and miRNAs analysis in relation to dairy cattle fertility - Ying Zhang; Rémi Labrecque; Patricia Tremblay; Clément Plessis; Pascal Dufour; Hélène Martin; Marc André Sirard (Theriogenology, 2024)

Early Responses to Crown Modification of California Black Oak Sprouts Initiated by High-Severity Wildfire - Martin Ritchie; John-Pascal Berrill; Ethan Hammett; Jonathan W Long (Journal of Forestry, 2024)
Hardwoods resprouting after wildfire or cutting develop as multistemmed clumps that gradually self-thin over time. There is increasing interest in thinning of sprouting species to accelerate the formation of tree characteristics important to indigenous cultural practices and wildlife such as large-diameter stems, large branches, broad crowns, and acorn production. We compared responses to three thinning treatments applied to black oak (Quercus kelloggii) resprouting after high-severity wildfire throughout northern California, USA. Basal area increment of the dominant stem was greatest after only one stem was retained, intermediate after three stems were retained, and lowest within unthinned oaks. Unwanted resprouting in response to the thinning was minimized by retaining three stems. Acorn production tended to increase as time elapsed since the fire (i.e., larger, older sprouts) but varied among sites and was noted as early as six years after fire at one site. More study is needed to test for the effects of thinning timing and intensity on the acceleration of acorn production as well as stem, branch, and crown size development over time.

Experimental erosion of microbial diversity decreases soil CH 4 consumption rates - Elvira Schnyder; Paul L. E. Bodelier; Martin Hartmann; Ruth Henneberger; Pascal A. Niklaus (Ecology, 2023)
Biodiversity‐ecosystem functioning (BEF) experiments have predominantly focused on communities of higher organisms, in particular plants, with comparably little known to date about the relevance of biodiversity for microbially driven biogeochemical processes. Methanotrophic bacteria play a key role in Earth's methane (CH 4 ) cycle by removing atmospheric CH 4 and reducing emissions from methanogenesis in wetlands and landfills. Here, we used a dilution‐to‐extinction approach to simulate diversity loss in a methanotrophic landfill cover soil community. Replicate samples were diluted 10 1 –10 7 ‐fold, preincubated under a high CH 4 atmosphere for microbial communities to recover to comparable size, and then incubated for 86 days at constant or diurnally cycling temperature. We hypothesize that (1) CH 4 consumption decreases as methanotrophic diversity is lost, and (2) this effect is more pronounced under variable temperatures. Net CH 4 consumption was determined by gas chromatography. Microbial community composition was determined by DNA extraction and sequencing of amplicons specific to methanotrophs and bacteria ( pmoA and 16S gene fragments). The richness of operational taxonomic units (OTU) of methanotrophic and nonmethanotrophic bacteria decreased approximately linearly with log ‐dilution. CH 4 consumption decreased with the number of OTUs lost, independent of community size. These effects were independent of temperature cycling. The diversity effects we found occured in relatively diverse communities, challenging the notion of high functional redundancy mediating high resistance to diversity erosion in natural microbial systems. The effects also resemble the ones for higher organisms, suggesting that BEF relationships are universal across taxa and spatial scales.

Do temporal and spatial heterogeneity modulate biodiversity–functioning relationships in com-munities of methanotrophic bacteria? - Elvira Schnyder; Paul L.E. Bodelier; Martin Hartmann; Ruth Henneberger; Pascal A. Niklaus (Soil Biology and Biochemistry, 2023)

Regional variation in deadwood decay of 13 tree species: Effects of climate, soil and forest structure - Pascal Edelmann; Wolfgang W. Weisser; Didem Ambarlı; Claus Bässler; François Buscot; Martin Hofrichter; Björn Hoppe; Harald Kellner; Cynthia Minnich; Julia Moll; Derek Persoh; Sebastian Seibold; et al. (Forest Ecology and Management, 2023)

Duplicate prescriptions in the emergency department: a retrospective cohort study - Johannes Heck; Benjamin Krichevsky; Adrian Groh; Martin Schulze Westhoff; Hans Laser; Swetlana Gerbel; Patrick-Pascal Strunz; Carsten Schumacher; Martin Klietz; Dirk O. Stichtenoth; Christoph Höner zu Siederdissen; Olaf Krause (European Journal of Clinical Pharmacology, 2023)
Purpose To determine the nature and frequency of duplicate prescriptions (DPs) in the emergency department (ED) by utilization of a novel categorization of DPs which differentiates between appropriate DPs (ADPs) and potentially inappropriate DPs (PIDPs). Methods In this retrospective cohort study, adult patients who presented to the ED for internal medicine of a large university hospital in northern Germany in 2018 and 2019 were screened for the presence of DPs. Descriptive statistical methods were used to characterize the nature and frequency of PIDPs compared to the frequency of ADPs. Results A total of 4208 patients were enrolled into the study. The median age of the study population was 63 years (interquartile range (IQR) 48–77), 53.9% were female. The patients took a median of 5 drugs (IQR 3–9). 10.9% of the study population were affected by at least one PIDP (at least one grade-1 PIDP: 6.1%; at least one grade-2 PIDP: 4.5%; at least one grade-3 PIDP: 1.1%). Non-opioid analgesics accounted for the majority of grade-1 PIDPs, while inhalatives were most frequently responsible for grade-2 and grade-3 PIDPs. Nearly half of the study population (48.6%) displayed at least one ADP. Conclusion PIDPs pose a frequent pharmacological challenge in the ED. The medication review should comprise a systematic screening for PIDPs with a particular focus on non-opioid analgesics and inhalatives. ADPs were detected more frequently than PIDPs, questioning the predominant notion in the medical literature that DPs are exclusively deleterious.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Dynamic branching in a neural network model for probabilistic prediction of sequences - Elif Köksal Ersöz; Pascal Chossat; Martin Krupa; Frédéric Lavigne (Journal of Computational Neuroscience, 2022)

Effects of psilocybin microdosing on awe and aesthetic experiences: a preregistered field and lab-based study - Michiel van Elk; George Fejer; Pascal Lempe; Luisa Prochazckova; Martin Kuchar; Katerina Hajkova; Josephine Marschall (Psychopharmacology, 2022)
There is an increased societal trend to engage in microdosing, in which small sub-hallucinogenic amounts of psychedelics are consumed on a regular basis. Following subjective reports that microdosing enhances the experience of nature and art, in the present study we set out to study the effects of psilocybin microdosing on feelings of awe and art perception. In this preregistered combined field- and lab-based study, participants took part in a microdosing workshop after which they volunteered to self-administer a psilocybin microdose or a placebo for three consecutive weeks, while the condition was kept blind to the participants and researchers. Following a 2-week break, the condition assignment was reversed. During each block, participants visited the lab twice to measure the effects of psilocybin microdosing vs. placebo. We used standardized measures of awe, in which participants reported their experiences in response to short videos or when viewing abstract artworks from different painters. Our confirmatory analyses showed that participants felt more awe in response to videos representing funny animals and moving objects in the microdosing compared to the placebo condition. However, about two-third of our participants were breaking blind to their experimental condition. Our exploratory findings suggest that expectancy-effects may be a driving factor underlying the subjective benefits of microdosing.

Soil Fungi Promote Biodiversity–Productivity Relationships in Experimental Communities of Young Trees - Bo Yang; Yu Liang; Bernhard Schmid; Martin Baruffol; Yangfan Li; Ling He; Yann Salmon; Qiuyang Tian; Pascal A. Niklaus; Keping Ma (Ecosystems, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Directional turnover towards larger‐ranged plants over time and across habitats - Ingmar R. Staude; Henrique M. Pereira; Gergana N. Daskalova; Markus Bernhardt‐Römermann; Martin Diekmann; Harald Pauli; Hans Van Calster; Mark Vellend; Anne D. Bjorkman; Jörg Brunet; Pieter De Frenne; Radim Hédl; et al. (Ecology Letters, 2022)
Species turnover is ubiquitous. However, it remains unknown whether certain types of species are consistently gained or lost across different habitats. Here, we analysed the trajectories of 1827 plant species over time intervals of up to 78 years at 141 sites across mountain summits, forests, and lowland grasslands in Europe. We found, albeit with relatively small effect sizes, displacements of smaller‐ by larger‐ranged species across habitats. Communities shifted in parallel towards more nutrient‐demanding species, with species from nutrient‐rich habitats having larger ranges. Because these species are typically strong competitors, declines of smaller‐ranged species could reflect not only abiotic drivers of global change, but also biotic pressure from increased competition. The ubiquitous component of turnover based on species range size we found here may partially reconcile findings of no net loss in local diversity with global species loss, and link community‐scale turnover to macroecological processes such as biotic homogenisation.

Ocean Integration: The Needs and Challenges of Effective Coordination Within the Ocean Observing System - Adèle Révelard; Joaquín Tintoré; Jacques Verron; Pierre Bahurel; John A. Barth; Mathieu Belbéoch; Jérôme Benveniste; Pascal Bonnefond; Eric P. Chassignet; Sophie Cravatte; Fraser Davidson; Brad deYoung; et al. (Frontiers in Marine Science, 2022)
Understanding and sustainably managing complex environments such as marine ecosystems benefits from an integrated approach to ensure that information about all relevant components and their interactions at multiple and nested spatiotemporal scales are considered. This information is based on a wide range of ocean observations using different systems and approaches. An integrated approach thus requires effective collaboration between areas of expertise in order to improve coordination at each step of the ocean observing value chain, from the design and deployment of multi-platform observations to their analysis and the delivery of products, sometimes through data assimilation in numerical models. Despite significant advances over the last two decades in more cooperation across the ocean observing activities, this integrated approach has not yet been fully realized. The ocean observing system still suffers from organizational silos due to independent and often disconnected initiatives, the strong and sometimes destructive competition across disciplines and among scientists, and the absence of a well-established overall governance framework. Here, we address the need for enhanced organizational integration among all the actors of ocean observing, focusing on the occidental systems. We advocate for a major evolution in the way we collaborate, calling for transformative scientific, cultural, behavioral, and management changes. This is timely because we now have the scientific and technical capabilities as well as urgent societal and political drivers. The ambition of the United Nations Decade of Ocean Science for Sustainable Development (2021–2030) and the various efforts to grow a sustainable ocean economy and effective ocean protection efforts all require a more integrated approach to ocean observing. After analyzing the barriers that currently prevent this full integration within the occidental systems, we suggest nine approaches for breaking down the silos and promoting better coordination and sharing. These recommendations are related to the organizational framework, the ocean science culture, the system of recognition and rewards, the data management system, the ocean governance structure, and the ocean observing drivers and funding. These reflections are intended to provide food for thought for further dialogue between all parties involved and trigger concrete actions to foster a real transformational change in ocean observing.

Strategies to prevent drug incompatibility during simultaneous multi-drug infusion in intensive care units: a literature review - Laura Négrier; Anthony Martin Mena; Gilles Lebuffe; Pascal Odou; Stéphanie Genay; Bertrand Décaudin (European Journal of Clinical Pharmacology, 2021)

Part-time work and other occupational risk factors for suicide among working women in the Swiss National Cohort - Pascal Wild; Nicolas Bovio; Irina Guseva Canu; Matthias Egger; Adrian Spörri; Marcel Zwahlen; Milo Puhan; Matthias Bopp; Martin Röösli; Michel Oris; Murielle Bochud (International Archives of Occupational and Environmental Health, 2021)
Objective The aim of this study was to describe the factors associated with mortality by suicide among working women focusing on work-related factors. Methods The study population consisted in all Swiss residents recorded in the 1990 and/or the 2000 compulsory national censuses and were linked to emigration and mortality registers. We selected all women aged 18–65 and at work at the official census dates. Following work-related variables were available: socio-economic status, weekly hours of work, the sector of activity and the job title coded according to the International Standard Classification of Occupations (ISCO). The risk of suicide was modelled using negative binomial regression. Results The cohort comprised 1,771,940 women and 2526 deaths by suicide corresponding to 24.9 million person-years. The most significant non-occupational predictors of suicide were age, period, civil status, religion, nationality and geographical regions. Adjusted on these factors, part-time work was associated with increased suicide rates. According to job codes, health and social activities, in particular care-worker had the highest suicide risks. Conclusion Suicide among working women depended on work-related factors even taking into account other socio-demographic factors.

Prey, management and landscape requirements of an endangered population of the Woodlark Lullula arborea in Southwest Germany - Verena Rösch; Pascal Aloisio; Martin H. Entling (Journal of Ornithology, 2021)
Vineyards can be valuable habitats for biodiversity conservation. For example, in Rhineland-Palatinate (Germany) over a third of the state’s critically endangered Woodlark ( Lullula arborea ) population breeds in vineyards along the western margin of the Upper Rhine Valley. We here aim to elucidate how local ground cover management, food availability and the proximity to settlements affect territory selection by this bird species in the region. As climate, site conditions and management differ greatly from more continental or Mediterranean wine-growing areas, conditions for Woodlark conservation may differ as well. We compared 26 Woodlark territories in vineyards with 26 nearby reference areas from which Woodlarks were absent. We recorded vineyard ground cover in the inter-rows (% cover) as well as vegetation height and composition (forbs vs. grasses). Arthropods were sampled using pitfall traps, since they are the main food resource of Woodlarks during the breeding season. In addition, the distance to built-up areas was measured. The vegetation in Woodlark territories was shorter (mean 14.2 vs. 19.6 cm) and more dominated by forbs (39% vs. 27% cover) than in absence areas. The vegetation cover in the inter-rows had no effect on Woodlark territory presence or absence. Woodlarks also favoured areas with a higher abundance of arthropods (mean abundance 69.1 vs. 57.5) and a greater distance to built-up areas (mean distance 554 vs. 373 m). We conclude that to promote the Woodlark in wine-growing areas, short, forb-rich swards should be created, facilitating arthropod detectability. This is likely to require low levels of nitrogen fertilization since fertilizers favour tall-growing grasses that outcompete forbs. Pesticide applications should be kept at a minimum to enhance arthropods as the main food source for Woodlarks and their chicks. In addition, the expansion of settlements into breeding areas of Woodlarks should be avoided.

A common soil temperature threshold for the upper limit of alpine grasslands in European mountains - Sarah Bürli; Jean-Paul Theurillat; Manuela Winkler; Andrea Lamprecht; Harald Pauli; Christian Rixen; Klaus Steinbauer; Sonja Wipf; Otar Abdaladze; Christopher Andrews; Peter Barančok; José Luis Benito-Alonso; et al. (Alpine Botany, 2021)
While climatic research about treeline has a long history, the climatic conditions corresponding to the upper limit of closed alpine grasslands remain poorly understood. Here, we propose a climatic definition for this limit, the ‘grassline’, in analogy to the treeline, which is based on the growing season length and the soil temperature. Eighty-seven mountain summits across ten European mountain ranges, covering three biomes (boreal, temperate, Mediterranean), were inventoried as part of the GLORIA project. Vascular plant cover was estimated visually in 326 plots of 1 × 1 m. Soil temperatures were measured in situ for 2–7 years, from which the length of the growing season and mean temperature were derived. The climatic conditions corresponding to 40% plant cover were defined as the thresholds for alpine grassland. Closed vegetation was present in locations with a mean growing season soil temperature warmer than 4.9 °C, or a minimal growing season length of 85 days, with the growing season defined as encompassing days with daily mean ≥ 1 °C. Hence, the upper limit of closed grasslands was associated with a mean soil temperature close to that previously observed at the treeline, and in accordance with physiological thresholds to growth in vascular plants. In contrast to trees, whose canopy temperature is coupled with air temperature, small-stature alpine plants benefit from the soil warmed by solar radiation and consequently, they can grow at higher elevations. Since substrate stability is necessary for grasslands to occur at their climatic limit, the grassline rarely appears as a distinct linear feature.

Thermal adaptation rather than demographic history drives genetic structure inferred by copy number variants in a marine fish - Hugo Cayuela; Yann Dorant; Claire Mérot; Martin Laporte; Eric Normandeau; Stéphane Gagnon‐Harvey; Marie Clément; Pascal Sirois; Louis Bernatchez (Molecular Ecology, 2021)
Increasing evidence shows that structural variants represent an overlooked aspect of genetic variation with consequential evolutionary roles. Among those, copy number variants (CNVs), including duplicated genomic regions and transposable elements (TEs), may contribute to local adaptation and/or reproductive isolation among divergent populations. Those mechanisms suppose that CNVs could be used to infer neutral and/or adaptive population genetic structure, whose study has been restricted to microsatellites, mitochondrial DNA and Amplified fragment length polymorphism markers in the past and more recently the use of single nucleotide polymorphisms (SNPs). Taking advantage of recent developments allowing CNV analysis from RAD‐seq data, we investigated how variation in fitness‐related traits, local environmental conditions and demographic history are associated with CNVs, and how subsequent copy number variation drives population genetic structure in a marine fish, the capelin ( Mallotus villosus ). We collected 1538 DNA samples from 35 sampling sites in the north Atlantic Ocean and identified 6620 putative CNVs. We found associations between CNVs and the gonadosomatic index, suggesting that six duplicated regions could affect female fitness by modulating oocyte production. We also detected 105 CNV candidates associated with water temperature, among which 20% corresponded to genomic regions located within the sequence of protein‐coding genes, suggesting local adaptation to cold water by means of gene sequence amplification. We also identified 175 CNVs associated with the divergence of three previously defined parapatric glacial lineages, of which 24% were located within protein‐coding genes, making those loci potential candidates for reproductive isolation. Lastly, our analyses unveiled a hierarchical, complex CNV population structure determined by temperature and local geography, which was in stark contrast to that inferred based on SNPs in a previous study. Our findings underline the complementarity of those two types of genomic variation in population genomics studies.

Abundance and biogeography of methanogenic and methanotrophic microorganisms across European streams - Magdalena Nagler; Nadine Praeg; Georg H. Niedrist; Katrin Attermeyer; Núria Catalán; Francesca Pilotto; Catherine Gutmann Roberts; Christoph Bors; Stefano Fenoglio; Miriam Colls; Sophie Cauvy‐Fraunié; Brian Doyle; et al. (Journal of Biogeography, 2021)
Aim Although running waters are getting recognized as important methane sources, large‐scale geographical patterns of microorganisms controlling the net methane balance of streams are still unknown. Here we aim at describing community compositions of methanogenic and methanotrophic microorganisms at large spatial scales and at linking their abundances to potential sediment methane production (PMP) and oxidation rates (PMO). Location The study spans across 16 European streams from northern Spain to northern Sweden and from western Ireland to western Bulgaria. Taxon Methanogenic archaea and methane‐oxidizing microorganisms. Methods To provide a geographical overview of both groups in a single approach, microbial communities and abundances were investigated via 16S rRNA gene sequencing, extracting relevant OTUs based on literature; both groups were quantified via quantitative PCR targeting mcrA and pmoA genes and studied in relation to environmental parameters, sediment PMP and PMO, and land use. Results Diversity of methanogenic archaea was higher in warmer streams and of methanotrophic communities in southern sampling sites and in larger streams. Anthropogenically altered, warm and oxygen‐poor streams were dominated by the highly efficient methanogenic families Methanospirillaceae , Methanosarcinaceae and Methanobacteriaceae , but did not harbour any specific methanotrophic organisms. Contrastingly, sediment communities in colder, oxygen‐rich waters with little anthropogenic impact were characterized by methanogenic Methanosaetaceae , Methanocellaceae and Methanoflorentaceae and methanotrophic Methylococcaceae and Cd . Methanoperedens. Representatives of the methanotrophic Crenotrichaceae and Methylococcaceae as well as the methanogenic Methanoregulaceae were characteristic for environments with larger catchment area and higher discharge. PMP increased with increasing abundance of methanogenic archaea, while PMO rates did not show correlations with abundances of methane‐oxidizing bacteria. Main conclusions Methanogenic and methanotrophic communities grouping into three habitat types suggest that future climate‐ and land use changes may influence the prevailing microbes involved in the large‐scale stream‐related methane cycle, favouring the growth of highly efficient hydrogenotrophic methane producers. Based on these results, we expect global change effect on PMP rates to especially impact rivers adjacent to anthropogenically disturbed land uses.

The GenTree Leaf Collection: Inter‐ and intraspecific leaf variation in seven forest tree species in Europe - Raquel Benavides; Bárbara Carvalho; Cristina C. Bastias; David López‐Quiroga; Antonio Mas; Stephen Cavers; Alan Gray; Audrey Albet; Ricardo Alía; Olivier Ambrosio; Filippos Aravanopoulos; Francisco Auñón; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait variation within species can reveal plastic and/or genetic responses to environmental gradients, and may indicate where local adaptation has occurred. Here, we present a dataset of rangewide variation in leaf traits from seven of the most ecologically and economically important tree species in Europe. Sample collection and trait assessment are embedded in the GenTree project (EU‐Horizon 2020), which aims at characterizing the genetic and phenotypic variability of forest tree species to optimize the management and sustainable use of forest genetic resources. Our dataset captures substantial intra‐ and interspecific leaf phenotypic variability, and provides valuable information for studying the relationship between ecosystem functioning and trait variability of individuals, and the response and resilience of species to environmental changes. Main types of variable contained We chose morphological and chemical characters linked to trade‐offs between acquisition and conservation of resources and water use, namely specific leaf area, leaf size, carbon and nitrogen content and their ratio, and the isotopic signature of stable isotope 13 C and 15 N in leaves. Spatial location and grain We surveyed between 18 and 22 populations per species, 141 in total, across Europe. Time period Leaf sampling took place between 2016 and 2017. Major taxa and level of measurement We sampled at least 25 individuals in each population, 3,569 trees in total, and measured traits in 35,755 leaves from seven European tree species, i.e. the conifers Picea abies , Pinus pinaster and Pinus sylvestris , and the broadleaves Betula pendula , Fagus sylvatica , Populus nigra and Quercus petraea . Software format The data files are in ASCII text, tab delimited, not compressed.

Spatial Distributions of Surface Sedimentary Organics and Sediment Profile Image Characteristics in a High-Energy Temperate Marine RiOMar: The West Gironde Mud Patch - Bastien Lamarque; Bruno Deflandre; Adriana Galindo Dalto; Sabine Schmidt; Alicia Romero-Ramirez; Frédéric Garabetian; Nicolas Dubosq; Mélanie Diaz; Florent Grasso; Aldo Sottolichio; Guillaume Bernard; Hervé Gillet; et al. (Journal of Marine Science and Engineering, 2021)
The spatial distributions of (1) surface sediment characteristics (D0.5, Sediment Surface Area (SSA), Particulate Organic Carbon (POC), Chlorophyll-a (Chl-a), Phaeophytin-a (Phaeo-a), Total and Enzymatically Hydrolyzable Amino Acids (THAA, EHAA), δ13C) and (2) sediment profile image (apparent Redox Potential Discontinuity (aRPD), numbers and depths of biological traces) characteristics were quantified based on the sampling of 32 stations located within the West Gironde Mud Patch (Bay of Biscay, NE Atlantic) in view of (1) assessing the spatial structuration of a temperate river-dominated ocean margin located in a high-energy area, (2) disentangling the impacts of hydrodynamics and bottom trawling on this structuration, and (3) comparing the West Gironde Mud Patch with the Rhône River Prodelta (located in a low-energy area). Results support the subdivision of the West Gironde Mud Patch in a proximal and a distal part and show (1) the existence of depth gradients in surface sedimentary organics characteristics and bioturbation within the distal part; (2) no evidence for a significant effect of bottom trawling, as opposed to Bottom Shear Stress, on the West Gironde Mud Patch spatial structuration; and (3) major discrepancies between spatial structuration in the West Gironde Mud Patch and the Rhône River Prodelta, which were attributed to differences in tidal regimes, sedimentation processes, and local hydrodynamics, which is in agreement with current river-dominated ocean margin typologies.

Sediment source fingerprinting: benchmarking recent outputs, remaining challenges and emerging themes - Adrian L. Collins; Martin Blackwell; Pascal Boeckx; Charlotte-Anne Chivers; Monica Emelko; Olivier Evrard; Ian Foster; Allen Gellis; Hamid Gholami; Steve Granger; Paul Harris; Arthur J. Horowitz; et al. (Journal of Soils and Sediments, 2020)
Purpose This review of sediment source fingerprinting assesses the current state-of-the-art, remaining challenges and emerging themes. It combines inputs from international scientists either with track records in the approach or with expertise relevant to progressing the science. Methods Web of Science and Google Scholar were used to review published papers spanning the period 2013–2019, inclusive, to confirm publication trends in quantities of papers by study area country and the types of tracers used. The most recent (2018–2019, inclusive) papers were also benchmarked using a methodological decision-tree published in 2017. Scope Areas requiring further research and international consensus on methodological detail are reviewed, and these comprise spatial variability in tracers and corresponding sampling implications for end-members, temporal variability in tracers and sampling implications for end-members and target sediment, tracer conservation and knowledge-based pre-selection, the physico-chemical basis for source discrimination and dissemination of fingerprinting results to stakeholders. Emerging themes are also discussed: novel tracers, concentration-dependence for biomarkers, combining sediment fingerprinting and age-dating, applications to sediment-bound pollutants, incorporation of supportive spatial information to augment discrimination and modelling, aeolian sediment source fingerprinting, integration with process-based models and development of open-access software tools for data processing. Conclusions The popularity of sediment source fingerprinting continues on an upward trend globally, but with this growth comes issues surrounding lack of standardisation and procedural diversity. Nonetheless, the last 2 years have also evidenced growing uptake of critical requirements for robust applications and this review is intended to signpost investigators, both old and new, towards these benchmarks and remaining research challenges for, and emerging options for different applications of, the fingerprinting approach.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Using stable isotope analysis to determine the effects of ocean acidification and warming on trophic interactions in a maerl bed community - Erwann Legrand; Sophie Martin; Cédric Leroux; Pascal Riera (Marine Ecology, 2020)
Ocean acidification and warming are likely to affect the structure and functioning of marine benthic communities. This study experimentally examined the effects of ocean acidification and warming on trophic interactions within a maerl bed community by using stable carbon and nitrogen isotope analysis. Two three‐month experiments were conducted in winter and summer seasons with four different combinations of pCO 2 (ambient and elevated pCO 2 ) and temperature (ambient and +3°C). Experimental assemblages were created in tanks held in the laboratory and were composed of calcareous ( Lithothamnion corallioides ) and fleshy algae ( Rhodymenia ardissonei , Solieria chordalis, and Ulva sp.), gastropods ( Gibbula magus and Jujubinus exasperatus ), and sea urchins ( Psammechinus miliaris ). Our results showed higher seaweed availability for grazers in summer than winter. Therefore, grazers were able to adapt their diet seasonally. Increased pCO 2 and temperature did not modify the trophic structure in winter, while shifts in the contribution of seaweed were found in summer. Combined acidification and warming increased the contribution of biofilm in gastropods diet in summer conditions. Psammechinus miliaris mostly consumed L. corallioides under ambient conditions, while the alga S. chordalis became the dominant food source under high pCO 2 in summer. Predicted changes in pCO 2 and temperature had complex effects on assemblage trophic structure. Direct effects of acidification and warming on seaweed metabolism may modify their abundance and biomass, affecting their availability for grazers. Climate change may also modify seaweeds' nutritive value and their palatability for grazers. The grazers we investigated were able to change their diet in response to changes in algal assemblages, an advantage given that warming and acidification alter the composition of algal communities.

Effect of pelagic longline bait type on species selectivity: a global synthesis of evidence - Eric Gilman; Milani Chaloupka; Pascal Bach; Hannah Fennell; Martin Hall; Michael Musyl; Susanna Piovano; Francois Poisson; Liming Song (Reviews in Fish Biology and Fisheries, 2020)
Fisheries can profoundly affect bycatch species with ‘slow’ life history traits. Managing bait type offers one tool to control species selectivity. Different species and sizes of marine predators have different prey, and hence bait, preferences. This preference is a function of a bait’s chemical, visual, acoustic and textural characteristics and size, and for seabirds the effect on hook sink rate is also important. We conducted a global meta-analysis of existing estimates of the relative risk of capture on different pelagic longline baits. We applied a Bayesian random effects meta-analytic regression modelling approach to estimate overall expected bait-specific catch rates. For blue shark and marine turtles, there were 34% (95% HDI: 4–59%) and 60% (95% HDI: 44–76%) significantly lower relative risks of capture on forage fish bait than squid bait, respectively. Overall estimates of bait-specific relative risk were not significantly different for seven other assessed taxa. The lack of a significant overall estimate of relative capture risk for pelagic shark species combined but significant effect for blue sharks suggests there is species-specific variability in bait-specific catch risk within this group. A qualitative literature review suggests that tunas and istiophorid billfishes may have higher catch rates on squid than fish bait, which conflicts with reducing marine turtle and blue shark catch rates. The findings from this synthesis of quantitative and qualitative evidence support identifying economically viable bycatch management measures with acceptable tradeoffs when multispecies conflicts are unavoidable, and highlight research priorities for global pelagic longline fisheries.

A Decision Support System for Determining Sugarcane Pest Reservoir - Pierre Martin; Pierre Silvie; Pascal Marnotte; François-Régis Goebel (Sugar Tech, 2020)

Heterogeneity of the rice microbial community of the Chinese centuries‐old Honghe Hani rice terraces system - Pascal Alonso; Laurence Blondin; Pierre Gladieux; Frédéric Mahé; Hervé Sanguin; Romain Ferdinand; Denis Filloux; Eric Desmarais; Frédérique Cerqueira; Baihui Jin; Huichuan Huang; Xiahong He; et al. (Environmental Microbiology, 2020)
Summary The Honghe Hani rice terraces system (HHRTS) is a traditional rice cultivation system where Hani people cultivate remarkably diverse rice varieties. Recent introductions of modern rice varieties to the HHRTS have significantly increased the severity of rice diseases within the terraces. Here, we determine the impacts of these recent introductions on the composition of the rice‐associated microbial communities. We confirm that the HHRTS contains a range of both traditional HHRTS landraces and introduced modern rice varieties and find differences between the microbial communities of these two groups. However, this introduction of modern rice varieties has not strongly impacted the overall diversity of the HHRTS rice microbial community. Furthermore, we find that the rice varieties (i.e. groups of closely related genotypes) have significantly structured the rice microbial community composition (accounting for 15%–22% of the variance) and that the core microbial community of HHRTS rice plants represents less than 3.3% of all the microbial taxa identified. Collectively, our study suggests a highly diverse HHRTS rice holobiont (host with its associated microbes) where the diversity of rice hosts mirrors the diversity of their microbial communities. Further studies will be needed to better determine how such changes might impact the sustainability of the HHRTS.

Shared ancestral polymorphisms and chromosomal rearrangements as potential drivers of local adaptation in a marine fish - Hugo Cayuela; Quentin Rougemont; Martin Laporte; Claire Mérot; Eric Normandeau; Yann Dorant; Ole K. Tørresen; Siv Nam Khang Hoff; Sissel Jentoft; Pascal Sirois; Martin Castonguay; Teunis Jansen; et al. (Molecular Ecology, 2020)
Gene flow has tremendous importance for local adaptation, by influencing the fate of de novo mutations, maintaining standing genetic variation and driving adaptive introgression. Furthermore, structural variation as chromosomal rearrangements may facilitate adaptation despite high gene flow. However, our understanding of the evolutionary mechanisms impending or favouring local adaptation in the presence of gene flow is still limited to a restricted number of study systems. In this study, we examined how demographic history, shared ancestral polymorphism, and gene flow among glacial lineages contribute to local adaptation to sea conditions in a marine fish, the capelin ( Mallotus villosus ). We first assembled a 490‐Mbp draft genome of M. villosus to map our RAD sequence reads. Then, we used a large data set of genome‐wide single nucleotide polymorphisms (25,904 filtered SNPs) genotyped in 1,310 individuals collected from 31 spawning sites in the northwest Atlantic. We reconstructed the history of divergence among three glacial lineages and showed that they probably diverged from 3.8 to 1.8 million years ago and experienced secondary contacts. Within each lineage, our analyses provided evidence for large N e and high gene flow among spawning sites. Within the Northwest Atlantic lineage, we detected a polymorphic chromosomal rearrangement leading to the occurrence of three haplogroups. Genotype–environment associations revealed molecular signatures of local adaptation to environmental conditions prevailing at spawning sites. Our study also suggests that both shared polymorphisms among lineages, resulting from standing genetic variation or introgression, and chromosomal rearrangements may contribute to local adaptation in the presence of high gene flow.

Evaluation of Different Quality-Relevant Aspects of Closed System Transfer Devices (CSTDs) - Ahmed Besheer; Hanns-Christian Mahler; Anja Matter-Schwald; Sergio Mompart Barrenechea; Martin Vogt; Pascal Chalus; Pauline Heymes; Timothy Pillow; Andrea Kirste; Patrick Favrod; Susanne Joerg; Roman Mathaes (Pharmaceutical Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: When behavioural geographic differentiation matters: inter-populational comparison of aggressiveness and group structure in the European perch - Lola Toomey; Martin Bláha; Emilie Mauduit; Tatyana Vanina; Margot Baratçabal; Yannick Ledoré; Sami Vesala; Pascal Fontaine; Alain Pasquet; Thomas Lecocq (Aquaculture International, 2019)

When behavioural geographic differentiation matters: inter-populational comparison of aggressiveness and group structure in the European perch - Lola Toomey; Martin Bláha; Emilie Mauduit; Tatyana Vanina; Margot Baratçabal; Yannick Ledoré; Sami Vesala; Pascal Fontaine; Alain Pasquet; Thomas Lecocq (Aquaculture International, 2019)

Pilzliche Peroxygenasen: der Schlüssel zu C-H-Hydroxylierungen und mehr? - Pascal Püllmann; Martin J. Weissenborn (BIOspektrum, 2019)

Parental sex allocation and sex-specific survival drive offspring sex ratio bias in little owls - Matthias Tschumi; Jolanda Humbel; Joscha Erbes; Julien Fattebert; Jochen Fischer; Gerhard Fritz; Barbara Geiger; Ronald van Harxen; Bernd Hoos; Johanna Hurst; Lars Bo Jacobsen; Herbert Keil; et al. (Behavioral Ecology and Sociobiology, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Temperature-related mortality impacts under and beyond Paris Agreement climate change scenarios - Ana Maria Vicedo-Cabrera; Yuming Guo; Francesco Sera; Veronika Huber; Carl-Friedrich Schleussner; Dann Mitchell; Shilu Tong; Micheline de Sousa Zanotti Staglior Coelho; Paulo Hilario Nascimento Saldiva; Eric Lavigne; Patricia Matus Correa; Nicolas Valdes Ortega; et al. (Climatic Change, 2018)

Binding of pigments to the cyanobacterial high-light-inducible protein HliC - Mahendra Kumar Shukla; Manuel J. Llansola-Portoles; Martin Tichý; Andrew A. Pascal; Bruno Robert; Roman Sobotka (Photosynthesis Research, 2018)

Effect of temperature on an alga‐grazer trophic transfer: A dual stable isotope ( 13 C, 15 N) labeling experiment - Erwann Legrand; Sophie Martin; Cédric Leroux; Pascal Riera (Marine Ecology, 2018)
In this study, we examined the impact of temperature on the carbon and nitrogen trophic transfers from a macroalga to a macro‐grazer by the use of dual 13 C‐ and 15 N‐labeling. Using an experimental approach in mesocosms, individuals of the urchin Psammechinus miliaris were maintained for 1 month at 17°C (mean summer temperature in the Bay of Brest) and at 20°C (maximum summer temperature) and fed with 13 C‐ and 15 N‐labeled Solieria chordalis. The results showed that the urchins’ 13 C uptake was 0.30 µg 13 C g dry weight (DW) −1 at 17°C and 0.14 µg 13 C g DW −1 at 20°C at the end of the experiment. The lower uptake at the higher temperature may be attributed to a decrease in metabolic activity at 20°C, involving lower feeding and/or respiration rates. Conversely, no significant effect of temperature was detected on 15 N uptake. At the end of the experiment, the urchins’ 15 N uptake was 0.04 µg 15 N g DW −1 at 17°C and 0.03 µg 15 N g DW −1 at 20°C. This suggests that temperature may affect carbon and nitrogen trophic fluxes differently. The use of dual isotope labeling offers interesting prospects and needs to be further extended in order to better understand trophic interactions in marine communities and the consequences of current environmental changes, such as global warming.

Positive diversity‐functioning relationships in model communities of methanotrophic bacteria - Elvira Schnyder; Paul L. E. Bodelier; Martin Hartmann; Ruth Henneberger; Pascal A. Niklaus (Ecology, 2018)
Biodiversity enhances ecosystem functions such as biomass production and nutrient cycling. Although the majority of the terrestrial biodiversity is hidden in soils, very little is known about the importance of the diversity of microbial communities for soil functioning. Here, we tested effects of biodiversity on the functioning of methanotrophs, a specialized group of soil bacteria that plays a key role in mediating greenhouse gas emissions from soils. Using pure strains of methanotrophic bacteria, we assembled artificial communities of different diversity levels, with which we inoculated sterile soil microcosms. To assess the functioning of these communities, we measured methane oxidation by gas chromatography throughout the experiment and determined changes in community composition and community size at several time points by quantitative PCR and sequencing. We demonstrate that microbial diversity had a positive overyielding effect on methane oxidation, in particular at the beginning of the experiment. This higher assimilation of CH 4 at high diversity translated into increased growth and significantly larger communities towards the end of the study. The overyielding of mixtures with respect to CH 4 consumption and community size were positively correlated. The temporal CH 4 consumption profiles of strain monocultures differed, raising the possibility that temporal complementarity of component strains drove the observed community‐level strain richness effects; however, the community niche metric we derived from the temporal activity profiles did not explain the observed strain richness effect. The strain richness effect also was unrelated to both the phylogenetic and functional trait diversity of mixed communities. Overall, our results suggest that positive biodiversity–ecosystem‐function relationships show similar patterns across different scales and may be widespread in nature. Additionally, biodiversity is probably also important in natural methanotrophic communities for the ecosystem function methane oxidation. Therefore, maintaining soil conditions that support a high diversity of methanotrophs may help to reduce the emission of the greenhouse gas methane.

Population Pharmacokinetic and Pharmacodynamic Modeling of Artemisinin Resistance in Southeast Asia - Jesmin Lohy Das; Arjen M. Dondorp; Francois Nosten; Aung Pyae Phyo; Warunee Hanpithakpong; Pascal Ringwald; Pharath Lim; Nicholas J. White; Mats O. Karlsson; Martin Bergstrand; Joel Tarning (The AAPS Journal, 2017)

Tackling the numbers problem: Entwicklung nicht-nativer Enzymreaktionen - Michelle Kammel; Anja Knorrscheidt; Pascal Püllmann; Martin J. Weissenborn (BIOspektrum, 2017)

Pan-European inter-laboratory studies on a panel of in vitro cytotoxicity and pro-inflammation assays for nanoparticles - Jean-Pascal Piret; Olesja M. Bondarenko; Matthew S. P. Boyles; Martin Himly; Ana R. Ribeiro; Federico Benetti; Caroline Smal; Braulio Lima; Annegret Potthoff; Monica Simion; Elise Dumortier; Paulo Emilio C. Leite; et al. (Archives of Toxicology, 2017)

Can niche plasticity promote biodiversity–productivity relationships through increased complementarity? - Pascal A. Niklaus; Martin Baruffol; Jin‐Sheng He; Keping Ma; Bernhard Schmid (Ecology, 2017)
Most experimental biodiversity–ecosystem functioning research to date has addressed herbaceous plant communities. Comparably little is known about how forest communities will respond to species losses, despite their importance for global biogeochemical cycling. We studied tree species interactions in experimental subtropical tree communities with 33 distinct tree species mixtures and one, two, or four species. Plots were either exposed to natural light levels or shaded. Trees grew rapidly and were intensely competing above ground after 1.5 growing seasons when plots were thinned and the vertical distribution of leaves and wood determined by separating the biomass of harvested trees into 50 cm height increments. Our aim was to analyze effects of species richness in relation to the vertical allocation of leaf biomass and wood, with an emphasis on bipartite competitive interactions among species. Aboveground productivity increased with species richness. The community‐level vertical leaf and wood distribution depended on the species composition of communities. Mean height and breadth of species‐level vertical leaf and wood distributions did not change with species richness. However, the extra biomass produced by mixtures compared to monocultures of the component species increased when vertical leaf distributions of monocultures were more different. Decomposition of biodiversity effects with the additive partitioning scheme indicated positive complementarity effects that were higher in light than in shade. Selection effects did not deviate from zero, irrespective of light levels. Vertical leaf distributions shifted apart in mixed stands as consequence of competition‐driven phenotypic plasticity, promoting realized complementarity. Structural equation models showed that this effect was larger for species that differed more in growth strategies that were characterized by functional traits. In 13 of the 18 investigated two‐species mixtures, both species benefitted relative to intraspecific competition in monoculture. In the remaining five pairwise mixtures, the relative yield gain of one species exceeded the relative yield loss of the other species, resulting in a relative yield total ( RYT ) exceeding 1. Overall, our analysis indicates that richness–productivity relationships are promoted by interspecific niche complementarity at early stages of stand development, and that this effect is enhanced by architectural plasticity.

The rich sides of mountain summits – a pan‐European view on aspect preferences of alpine plants - Manuela Winkler; Andrea Lamprecht; Klaus Steinbauer; Karl Hülber; Jean‐Paul Theurillat; Frank Breiner; Philippe Choler; Siegrun Ertl; Alba Gutiérrez Girón; Graziano Rossi; Pascal Vittoz; Maia Akhalkatsi; et al. (Journal of Biogeography, 2016)
Aim In the alpine life zone, plant diversity is strongly determined by local topography and microclimate. We assessed the extent to which aspect and its relatedness to temperature affect plant species diversity, and the colonization and disappearance of species on alpine summits on a pan‐European scale. Location Mountain summits in Europe's alpine life zone. Methods Vascular plant species and their percentage cover were recorded in permanent plots in each cardinal direction on 123 summits in 32 regions across Europe. For a subset from 17 regions, resurvey data and 6‐year soil temperature series were available. Differences in temperature sum and Shannon index as well as species richness, colonization and disappearance of species among cardinal directions were analysed using linear mixed‐effects and generalised mixed‐effects models, respectively. Results Temperature sums were higher in east‐ and south‐facing aspects than in the north‐facing ones, while the west‐facing ones were intermediate; differences were smallest in northern Europe. The patterns of temperature sums among aspects were consistent among years. In temperate regions, thermal differences were reflected by plant diversity, whereas this relationship was weaker or absent on Mediterranean and boreal mountains. Colonization of species was positively related to temperature on Mediterranean and temperate mountains, whereas disappearance of species was not related to temperature. Main conclusions Thermal differences caused by solar radiation determine plant species diversity on temperate mountains. Advantages for plants on eastern slopes may result from the combined effects of a longer diurnal period of radiation due to convection cloud effects in the afternoon and the sheltered position against the prevailing westerly winds. In northern Europe, long summer days and low sun angles can even out differences among aspects. On Mediterranean summits, summer drought may limit species numbers on the warmer slopes. Warmer aspects support a higher number of colonization events. Hence, aspect can be a principal determinant of the pace of climate‐induced migration processes.

A comparative review of fisheries management experiences in the E uropean U nion and in other countries worldwide: I celand, A ustralia, and N ew Z ealand - Paul Marchal; Jesper Levring Andersen; Martin Aranda; Mike Fitzpatrick; Leyre Goti; Olivier Guyader; Gunnar Haraldsson; Aaron Hatcher; Troels Jacob Hegland; Pascal Le Floc'h; Claire Macher; Loretta Malvarosa; et al. (Fish and Fisheries, 2016)
This study compares the details and performance of fisheries management between the EU and a selection of other countries worldwide: Iceland, New Zealand, and Australia, which are considered in many respects to be among the most advanced in the world in fisheries management. Fisheries management in the EU , Iceland, Australia, and New Zealand has developed following different paths, despite being based on similar instruments and principles. Iceland, Australia, and New Zealand have been at the forefront of developing management practices such as stakeholder involvement, legally binding management targets (Australia, New Zealand), individual transferable quotas, and discard bans (Iceland, New Zealand). The EU has since the beginning of the 21st century taken significant steps to better involve stakeholders and establish quantitative targets through management plans, and a landing obligation is gradually being implemented from 2015 onward. The management of domestic fisheries resources in Australia, New Zealand, and Iceland has, overall, performed better than in the EU , in terms of conservation and economic efficiency. It should, however, be stressed that, compared to Australia, New Zealand, and Iceland, (i) initial over‐capacity was more of an issue in the EU when management measures became legally binding and also that (ii) EU has been progressive in developing common enforcement standards, on stocks shared by sovereign nations. The situation of EU fisheries has substantially improved over the period 2004–2013 in the northeast Atlantic, with fishery status getting close to that in the other jurisdictions, but the lack of recovery for Mediterranean fish stocks remains a concern.

Long-term efficacy and safety of etravirine-containing regimens in a real-life cohort of treatment-experienced HIV-1-infected patients - Clotilde Allavena; Christine Katlama; Laurent Cotte; Pierre Marie Roger; Pierre Delobel; Antoine Cheret; Claudine Duvivier; Isabelle Poizot-Martin; Bruno Hoen; André Cabie; Arnaud Cheret; Rima Lahoulou; et al. (Infectious Diseases, 2016)

An integrated pan‐tropical biomass map using multiple reference datasets - Valerio Avitabile; Martin Herold; Gerard B. M. Heuvelink; Simon L. Lewis; Oliver L. Phillips; Gregory P. Asner; John Armston; Peter S. Ashton; Lindsay Banin; Nicolas Bayol; Nicholas J. Berry; Pascal Boeckx; et al. (Global Change Biology, 2016)
We combined two existing datasets of vegetation aboveground biomass ( AGB ) ( Proceedings of the National Academy of Sciences of the United States of America , 108 , 2011, 9899; Nature Climate Change , 2 , 2012, 182) into a pan‐tropical AGB map at 1‐km resolution using an independent reference dataset of field observations and locally calibrated high‐resolution biomass maps, harmonized and upscaled to 14 477 1‐km AGB estimates. Our data fusion approach uses bias removal and weighted linear averaging that incorporates and spatializes the biomass patterns indicated by the reference data. The method was applied independently in areas (strata) with homogeneous error patterns of the input (Saatchi and Baccini) maps, which were estimated from the reference data and additional covariates. Based on the fused map, we estimated AGB stock for the tropics (23.4 N–23.4 S) of 375 Pg dry mass, 9–18% lower than the Saatchi and Baccini estimates. The fused map also showed differing spatial patterns of AGB over large areas, with higher AGB density in the dense forest areas in the Congo basin, Eastern Amazon and South‐East Asia, and lower values in Central America and in most dry vegetation areas of Africa than either of the input maps. The validation exercise, based on 2118 estimates from the reference dataset not used in the fusion process, showed that the fused map had a RMSE 15–21% lower than that of the input maps and, most importantly, nearly unbiased estimates (mean bias 5 Mg dry mass ha −1 vs. 21 and 28 Mg ha −1 for the input maps). The fusion method can be applied at any scale including the policy‐relevant national level, where it can provide improved biomass estimates by integrating existing regional biomass maps as input maps and additional, country‐specific reference datasets.

Experimental Investigation of Pressure Applied on the Lower Leg by Elastic Compression Bandage - Fanette Chassagne; Frédéric Martin; Pierre Badel; Reynald Convert; Pascal Giraux; Jérôme Molimard (Annals of Biomedical Engineering, 2015)

Disjunct populations of E uropean vascular plant species keep the same climatic niches - Safaa Wasof; Jonathan Lenoir; Per Arild Aarrestad; Inger Greve Alsos; W. Scott Armbruster; Gunnar Austrheim; Vegar Bakkestuen; H. John B. Birks; Kari Anne Bråthen; Olivier Broennimann; Jörg Brunet; Hans Henrik Bruun; et al. (Global Ecology and Biogeography, 2015)
Aim Previous research on how climatic niches vary across species ranges has focused on a limited number of species, mostly invasive, and has not, to date, been very conclusive. Here we assess the degree of niche conservatism between distant populations of native alpine plant species that have been separated for thousands of years. Location European A lps and F ennoscandia. Methods Of the studied pool of 888 terrestrial vascular plant species occurring in both the A lps and F ennoscandia, we used two complementary approaches to test and quantify climatic‐niche shifts for 31 species having strictly disjunct populations and 358 species having either a contiguous or a patchy distribution with distant populations. First, we used species distribution modelling to test for a region effect on each species' climatic niche. Second, we quantified niche overlap and shifts in niche width (i.e. ecological amplitude) and position (i.e. ecological optimum) within a bi‐dimensional climatic space. Results Only one species (3%) of the 31 species with strictly disjunct populations and 58 species (16%) of the 358 species with distant populations showed a region effect on their climatic niche. Niche overlap was higher for species with strictly disjunct populations than for species with distant populations and highest for arctic–alpine species. Climatic niches were, on average, wider and located towards warmer and wetter conditions in the Alps. Main conclusion Climatic niches seem to be generally conserved between populations that are separated between the A lps and F ennoscandia and have probably been so for 10,000–15,000 years. Therefore, the basic assumption of species distribution models that a species' climatic niche is constant in space and time – at least on time scales 10 4 years or less – seems to be largely valid for arctic–alpine plants.

Transcription factor Yin-Yang 2 alters neuronal outgrowth in vitro - Martin Klar; Pascal Fenske; Fanny Rezza Vega; Christof Dame; Anja U. Bräuer (Cell and Tissue Research, 2015)

Fire ecology of C 3 and C 4 grasses depends on evolutionary history and frequency of burning but not photosynthetic type - Brad Ripley; Vernon Visser; Pascal-Antoine Christin; Sally Archibald; Tarryn Martin; Colin Osborne (Ecology, 2015)
Grasses using the C 4 photosynthetic pathway dominate frequently burned savannas, where the pathway is hypothesized to be adaptive. However, independent C 4 lineages also sort among different fire environments. Adaptations to fire may thus depend on evolutionary history, which could be as important as the possession of the C 4 photosynthetic pathway for life in these environments. Here, using a comparative pot experiment and controlled burn, we examined C 3 and C 4 grasses belonging to four lineages from the same regional flora, and asked the following questions: Do lineages differ in their responses to fire, are responses consistent between photosynthetic types, and are responses related to fire frequency in natural habitats? We found that in the C 4 Andropogoneae lineage, frost killed a large proportion of aboveground biomass and produced a large dry fuel load, which meant that only a small fraction of the living tissue was lost in the fire. C 3 species from the Paniceae and Danthonioideae lineages generated smaller fuel loads and lost more living biomass, while species from the C 4 lineage Aristida generated the smallest fuel loads and lost the most living tissue. Regrowth after the fire was more rapid and complete in the C 4 Andropogoneae and C 3 Paniceae, but incomplete and slower in the C 3 Danthonioideae and C 4 Aristida . Rapid recovery was associated with high photosynthetic rates, high specific leaf area, delayed flowering, and frequent fires in natural habitats. Results demonstrated that phylogenetic lineage was more important than photosynthetic type in determining the fire response of these grasses and that fire responses were related to the frequency that natural habitats burned.

Characterization of 24 polymorphic microsatellite markers for Silene nutans, a gynodioecious–gynomonoecious species, and cross-species amplification in other Silene species - Cécile Godé; Pascal Touzet; Hélène Martin; Emna Lahiani; Lynda F. Delph; Jean-François Arnaud (Conservation Genetics Resources, 2014)

Arrhythmogenic effects by local left ventricular stretch: effects of flecainide and streptomycin - Stefan Dhein; Christine Englert; Stephanie Riethdorf; Martin Kostelka; Pascal Maria Dohmen; Friedrich-Wilhelm Mohr (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Erratum to: EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

Resource partitioning among cladocerans in a littoral macrophyte zone: implications for the transfer of essential compounds - Hélène Masclaux; Gilles Bourdier; Pascal Riera; Martin J. Kainz; Lionel Jouve; Emilie Duffaud; Alexandre Bec (Aquatic Sciences, 2014)

Impact of climate change on the hydrogeology of two basins in northern France - Florence Habets; Julien Boé; Michel Déqué; Agnès Ducharne; Simon Gascoin; Ali Hachour; Eric Martin; Christian Pagé; Eric Sauquet; Laurent Terray; Dominique Thiéry; Ludovic Oudin; et al. (Climatic Change, 2013)

The simulation of European heat waves from an ensemble of regional climate models within the EURO-CORDEX project - Robert Vautard; Andreas Gobiet; Daniela Jacob; Michal Belda; Augustin Colette; Michel Déqué; Jesús Fernández; Markel García-Díez; Klaus Goergen; Ivan Güttler; Tomáš Halenka; Theodore Karacostas; et al. (Climate Dynamics, 2013)

Nutrient input from hemiparasitic litter favors plant species with a fast-growth strategy - Andreas Demey; Jeroen Staelens; Lander Baeten; Pascal Boeckx; Martin Hermy; Jens Kattge; Kris Verheyen (Plant and Soil, 2013)

Divergent evolutionary processes associated with colonization of offshore islands - Natália Martínková; Ross Barnett; Thomas Cucchi; Rahel Struchen; Marine Pascal; Michel Pascal; Martin C. Fischer; Thomas Higham; Selina Brace; Simon Y. W. Ho; Jean‐Pierre Quéré; Paul O'Higgins; et al. (Molecular Ecology, 2013)
Oceanic islands have been a test ground for evolutionary theory, but here, we focus on the possibilities for evolutionary study created by offshore islands. These can be colonized through various means and by a wide range of species, including those with low dispersal capabilities. We use morphology, modern and ancient sequences of cytochrome b ( cytb ) and microsatellite genotypes to examine colonization history and evolutionary change associated with occupation of the O rkney archipelago by the common vole ( M icrotus arvalis ), a species found in continental E urope but not in B ritain. Among possible colonization scenarios, our results are most consistent with human introduction at least 5100 bp (confirmed by radiocarbon dating). We used approximate B ayesian computation of population history to infer the coast of Belgium as the possible source and estimated the evolutionary timescale using a Bayesian coalescent approach. We showed substantial morphological divergence of the island populations, including a size increase presumably driven by selection and reduced microsatellite variation likely reflecting founder events and genetic drift. More surprisingly, our results suggest that a recent and widespread cytb replacement event in the continental source area purged cytb variation there, whereas the ancestral diversity is largely retained in the colonized islands as a genetic ‘ark’. The replacement event in the continental M . arvalis was probably triggered by anthropogenic causes (land‐use change). Our studies illustrate that small offshore islands can act as field laboratories for studying various evolutionary processes over relatively short timescales, informing about the mainland source area as well as the island.

Effects of two contrasting hemiparasitic plant species on biomass production and nitrogen availability - Andreas Demey; Els Ameloot; Jeroen Staelens; An De Schrijver; Gorik Verstraeten; Pascal Boeckx; Martin Hermy; Kris Verheyen (Oecologia, 2013)

Summer temperatures in Europe and land heat fluxes in observation-based data and regional climate model simulations - Annemiek I. Stegehuis; Robert Vautard; Philippe Ciais; Adriaan J. Teuling; Martin Jung; Pascal Yiou (Climate Dynamics, 2013)

Sex ratios and clonal growth in dioecious Populus euphratica Oliv., Xinjiang Prov., Western China - Anne Petzold; Tanja Pfeiffer; Florian Jansen; Pascal Eusemann; Martin Schnittler (Trees, 2013)

FLOHOF 2007: an overview of the mesoscale meteorological field campaign at Hofsjökull, Central Iceland - Joachim Reuder; Markus Ablinger; Hálfdán Ágústsson; Pascal Brisset; Sveinn Brynjólfsson; Markus Garhammer; Tómas Jóhannesson; Marius O. Jonassen; Rafael Kühnel; Stephan Lämmlein; Tor de Lange; Christian Lindenberg; et al. (Meteorology and Atmospheric Physics, 2012)

Uptake of a randomized breast cancer prevention trial comparing letrozole to placebo in BRCA1/2 mutations carriers: the LIBER trial - Pascal Pujol; Christine Lasset; Pascaline Berthet; Catherine Dugast; Suzette Delaloge; Jean-Pierre Fricker; Isabelle Tennevet; Nathalie Chabbert-Buffet; Pascale This; Karen Baudry; Jerome Lemonnier; Lise Roca; et al. (Familial Cancer, 2012)

Variation in GUS activity in vegetatively propagated Hevea brasiliensis transgenic plants - Ludovic Lardet; Julie Leclercq; Elise Bénistan; Florence Dessailly; Gérald Oliver; Florence Martin; Pascal Montoro (Plant Cell Reports, 2011)

How might science misdirect policy? Insights into the threats and consequences of invasive species - Martin A. Schlaepfer; Michel Pascal; Mark A. Davis (Journal of Consumer Protection and Food Safety, 2011)

Soil microbial diversity: an ISO standard for soil DNA extraction - Laurent Philippot; Cristina Abbate; Antonio Bispo; Thierry Chesnot; Sara Hallin; Philippe Lemanceau; Kristina Lindström; Pascal Pandard; Esperanza Romero; Michael Schloter; Pascal Simonet; Kornelia Smalla; et al. (Journal of Soils and Sediments, 2010)

Environmental Radioxenon Levels in Europe: a Comprehensive Overview - Paul R. J. Saey; Clemens Schlosser; Pascal Achim; Matthias Auer; Anders Axelsson; Andreas Becker; Xavier Blanchard; Guy Brachet; Luis Cella; Lars-Erik De Geer; Martin B. Kalinowski; Gilbert Le Petit; et al. (Pure and Applied Geophysics, 2010)

Value of an urban habitat for the native Mediterranean avifauna - Sabina Amparo Caula; Clélia Sirami; Pascal Marty; Jean-Louis Martin (Urban Ecosystems, 2010)

Validity of a Power Law Approach to Model Tablet Strength as a Function of Compaction Pressure - Bastian Kloefer; Pascal Henschel; Martin Kuentz (AAPS PharmSciTech, 2010)

Harmonin-b, an actin-binding scaffold protein, is involved in the adaptation of mechanoelectrical transduction by sensory hair cells - Nicolas Michalski; Vincent Michel; Elisa Caberlotto; Gaelle M. Lefèvre; Alexander F. J. van Aken; Jean-Yves Tinevez; Emilie Bizard; Christophe Houbron; Dominique Weil; Jean-Pierre Hardelin; Guy P. Richardson; Corné J. Kros; et al. (Pflügers Archiv - European Journal of Physiology, 2009)

Root suckering patterns in Populus euphratica (Euphrates poplar, Salicaceae) - Martin Wiehle; Pascal Eusemann; Niels Thevs; Martin Schnittler (Trees, 2009)

Impact of hemiparasitic Rhinanthus angustifolius and R. minor on nitrogen availability in grasslands - Els Ameloot; Greet Verlinden; Pascal Boeckx; Kris Verheyen; Martin Hermy (Plant and Soil, 2008)

A mutation in KIR3DS1 that results in truncation and lack of cell surface expression - Maureen P. Martin; Véronique Pascal; Meredith Yeager; John Phair; Gregory D. Kirk; Keith Hoots; Stephen J. O’Brien; Stephen K. Anderson; Mary Carrington (Immunogenetics, 2007)

A mutation in KIR3DS1 that results in truncation and lack of cell surface expression - Maureen P. Martin; Véronique Pascal; Meredith Yeager; John Phair; Gregory D. Kirk; Keith Hoots; Stephen J. O’Brien; Stephen K. Anderson; Mary Carrington (Immunogenetics, 2007)

A mutation in KIR3DS1 that results in truncation and lack of cell surface expression - Maureen P. Martin; Véronique Pascal; Meredith Yeager; John Phair; Gregory D. Kirk; Keith Hoots; Stephen J. O’Brien; Stephen K. Anderson; Mary Carrington (Immunogenetics, 2007)

Effect of exogenous calcium on post-thaw growth recovery and subsequent plant regeneration of cryopreserved embryogenic calli of Hevea brasiliensis (Müll. Arg.) - Ludovic Lardet; Florence Martin; Florence Dessailly; Marc-Philippe Carron; Pascal Montoro (Plant Cell Reports, 2007)

Conflicts management, social capital and adoption of agroforestry technologies: empirical findings from the highlands of southwestern Uganda - Pascal C. Sanginga; Rick N. Kamugisha; Adrienne M. Martin (Agroforestry Systems, 2007)

Influence of Dyslipidemia on Moxidectin Distribution in Plasma Lipoproteins and on its Pharmacokinetics - Mohamad Firas Bassissi; Michel Alvinerie; Pascal Guy Pierre Martin; Bertrand Perret; Anne Lespine (Pharmaceutical Research, 2006)

Displacement of an herbaceous plant species community by mycorrhizal and non-mycorrhizal Gmelina arborea, an exotic tree, grown in a microcosm experiment - Arsene Sanon; Pascal Martin; Jean Thioulouse; Christian Plenchette; Rodolphe Spichiger; Michel Lepage; Robin Duponnois (Mycorrhiza, 2006)

First data on growth of cultured brown meagre Sciaena umbra using diets with different protein and fat contents - Stavros CHATZIFOTIS; Adriana VILLAMOR MARTIN-PRAT; Nikos LIMBERIS; Nikos PAPANDROULAKIS; Pascal DIVANACH (Fisheries Science, 2006)

Efficient Agrobacterium tumefaciens-mediated transformation of embryogenic calli and regeneration of Hevea brasiliensis Müll Arg. plants - Géraldine Blanc; Christelle Baptiste; Gérald Oliver; Florence Martin; Pascal Montoro (Plant Cell Reports, 2006)

The sigma1 (?1) receptor activation is a key step for the reactivation of cocaine conditioned place preference by drug priming - Pascal Romieu; Johann Meunier; Dborah Garcia; Nadia Zozime; Rmi Martin-Fardon; WayneD. Bowen; Tangui Maurice (Psychopharmacology, 2004)

Dual Mesh Method for Upscaling in Waterflood Simulation - Pascal Audigane; Martin J. Blunt (Transport in Porous Media, 2004)